حقوق االنسان في النصوص الدولية و االقليمية - أ. د. عبد الغفور كريم- الجامعة اللبنانية الفرنسية - اربيل,; د. شفان أحمد قادر- الجامعة اللبنانية الفرنسية - اربيل, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The global interest in human rights in the last two decades of the twentieth century and the twenty-first century has taken a great deal of attention. Some thinkers of this century have launched the century of democracy and human rights. Many articles, studies and publications have emerged and international and regional conventions have been adopted to address various aspects and developments related to this subject. The issue of human rights is no longer an individual issue, which is dealt with within the scope of domestic laws and regulations. Today, it is a universal issue, which means that it is no longer the property of a particular people or the essence of a specific idea or the result of a specific experience of a State. The rights of peoples and nations wherever they exist and to any religion, race, nation or state Human rights in contemporary democratic systems are at the center of all rights, and these rights are of no value to them if they are not dedicated to serving them and preserving their dignity. Therefore, we have seen that attention has transcended the boundaries of states and the scope of local constitutions. This subject has become universal. International conventions and agreements, foremost of which are the Universal Declaration of Human Rights (1948), the International Covenants of 1969 and the Rome Convention of 1998, and the United Nations has endeavored to internationalize it and make it part of international public law If the subject of human rights becomes the concern of the rulers, leaders and political systems, and everyone aspires to protect himself by legitimacy and to remove the charge of tyranny and dictatorship in all his practices and everyone is competing in the beautification and decoration of his constitutions and legislation in terms of respect for the human rights issue And care . The Kurdistan Region of Iraq has its own legislation in the field of human rights and has reached the ranks of the developed countries. The Government of the Territory has all the capabilities to implement international and domestic texts and to strictly prevent violations of human rights.